2020
DOI: 10.3390/rs12203437
|View full text |Cite
|
Sign up to set email alerts
|

Using the MODIS Sensor for Snow Cover Modeling and the Assessment of Drought Effects on Snow Cover in a Mountainous Area

Abstract: Snow is one of the essential factors in hydrology, freshwater resources, irrigation, travel, pastimes, floods, avalanches, and vegetation. In this study, the snow cover of the northern and southern slopes of Alborz Mountains in Iran was investigated by considering two issues: (1) Estimating the snow cover area and the (2) effects of droughts on snow cover. The snow cover data were monitored by images obtained from the Moderate Resolution Imaging Spectroradiometer (MODIS) sensor. The meteorological data (includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 35 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…The applied models led to desirable predictions in arid, semi-arid, and Mediterranean climates, while humid climate provided the weakest predictions. Aghelpour et al (2020c) investigated the snow cover of the Northern and Southern slopes of Alborz Mountains in Iran by considering two issues: (1) estimating the snow cover area and (2) investigating the effects of droughts on snow cover. The results showed that the effects of a drought event on the snow cover area would remain up to 5 (or 6) months in the region.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…The applied models led to desirable predictions in arid, semi-arid, and Mediterranean climates, while humid climate provided the weakest predictions. Aghelpour et al (2020c) investigated the snow cover of the Northern and Southern slopes of Alborz Mountains in Iran by considering two issues: (1) estimating the snow cover area and (2) investigating the effects of droughts on snow cover. The results showed that the effects of a drought event on the snow cover area would remain up to 5 (or 6) months in the region.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Forecasting the evapotranspiration rates, through providing information on the future status of evapotranspiration at different time scales can be of great help in making appropriate decisions, planning as well as applying management methods of water resources. Data-driven models such as stochastic and artificial intelligence methods are efficient approaches that have shown good performance in modeling and predicting hydrometeorological variables in recent years (Aghelpour et al, 2021c;Mohammadi et al, 2020;Aghelpour et al 2020b). Karbasi (2018) used AIs in forecasting ET0 for 1, 2, 3, 7, 10, 14, 18, 24, and 30 days' horizons.…”
Section: Introductionmentioning
confidence: 99%
“…This type of neural network is one type of multipurpose basic and approximating radial neural networks for smooth functions. GRNN is a three-layer neural network in which, like the other neural networks [48]. The number of neurons existent on the first and last layers is, respectively, equal to the dimensions of the input and output vectors, but, unlike the other networks, the number of the neurons in the hidden layer of GRNN is equal to the number of the observed data.…”
Section: Generalized Regression Neural Network (Grnn)mentioning
confidence: 99%
“…This type of neural network uses normal efficiency function in each of the neurons of the hidden layer, and the data inputted into this function for each neuron include the Euclidean distance between the input and observed data related to that neuron. See the sources for complementary information on GRNN [45,48,49].…”
Section: Generalized Regression Neural Network (Grnn)mentioning
confidence: 99%